Facial angiofibromas of tuberous sclerosis treated with topical sirolimus in an Indian patient - Resham J Vasani (Wolters Kluwer Medknow Publications, 2015)
Facial angiofibromas are the most visible and unsightly of all the cutaneous manifestations of tuberous sclerosis (TSC). A 17-year-old female, a known case of TSC, presented for the treatment of cosmetically disfiguring facial angiofibromas. She was started on twice daily application of 0.1% sirolimus ointment prepared from crushed tablets of sirolimus compounded in white soft paraffin. After 3 months of use, there was visible decrease in the erythema and the size of the angiofibromas. In an attempt to accelerate the response, the concentration was further increased to 1% sirolimus which was used for a month, resulting in a decrease not only in the size and redness but also in the number of the angiofibromas. The patient did not experience any cutaneous or systemic complications related to therapy. Sirolimus belongs to a novel class of anticancer drugs known as mTOR (mammalian target of Rapamycin) inhibitors. Sirolimus has been used as a targeted therapy for the renal and neurological manifestations of TSC. Topical preparation of sirolimus is not commercially available till date and hence preparations from crushed tablets or oral solution of sirolimus have been used with beneficial effects in treatment of angiofibromas especially in younger patients with flatter lesions. Randomized controlled trials are necessary to enable us to confirm the efficacy, long-term safety, the optimal dosage and possibility of reappearance once the drug is withdrawn. This is possibly the first case report of the use of topical sirolimus in India.